Kepedulian Generasi Z Terhadap Isu Global - Azizah Alawiyah; Milla Aristia Dewari; Asa Nudiya (Lembaga Pengembangan Kinerja Dosen, 2025)
Generation Z or Gen Z is a generation that lives alongside the development of digital technology. The age of Gen Z is the age of the generation that will lead a nation in the future, for this reason, careful preparation is needed to form the characteristics needed by the world in the future, one of which is sensitivity to global issues. For this reason, the purpose of this research is to find out the role of Gen Z in obtaining information and responding to existing global issues. The research method in this study is a narrative review with a qualitative research type. The results show that Gen Z's concern can be seen from their sensitivity to global issues by being actively involved through social media platforms, for example about maintaining mental stability, environmental issues such as climate change, and so on.